Evolution of Molecular Targeted Cancer Therapy: Mechanisms of Drug Resistance and Novel Opportunities Identified by CRISPR-Cas9 Screening - Hou, Jue; He, Zongsheng; Liu, Tian; Chen, Dongfeng; Wang, Bin; Wen, Qinglian; Zheng, Xi (Frontiers in Oncology, 2022)
Molecular targeted therapy has revolutionized the landscape of cancer treatment due to better therapeutic responses and less systemic toxicity. However, therapeutic resistance is a major challenge in clinical settings that hinders continuous clinical benefits for cancer patients. In this regard, unraveling the mechanisms of drug resistance may identify new druggable genetic alterations for molecular targeted therapies, thus contributing to improved therapeutic efficacies. The recent rapid development of novel methodologies including CRISPR-Cas9 screening technology and patient-derived models provides powerful tools to dissect the underlying mechanisms of resistance to targeted cancer therapies. In this review, we update candidate therapeutic targets undergoing preclinical and clinical studies for various cancer types. More importantly, we discuss the applications and recent findings of high throughput CRISPR-Cas9 screening in deciphering potential mechanisms of unresponsiveness to these molecularly targeted therapies, which may lead to the discovery of novel opportunities for designing next-generation anti-cancer drugs.